2004
DOI: 10.1097/00000372-200410000-00004
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Immunohistochemistry in Atypical Cutaneous Fibrous Histiocytoma

Abstract: Atypical cutaneous fibrous histiocytoma is a rare variant of dermatofibroma/fibrous histiocytoma characterized by striking atypia, thus resembling atypical fibroxanthoma. We studied 9 examples of ACFH histopathologically and immunohistochemically to investigate the nature of these atypical cells. Histology revealed ill-defined skin nodules, which were polypoid in 6 cases. A minority of mononuclear and giant cells (< 5%) revealed striking pleomorphism and showed large nuclei with prominent nucleoli. Immunohisto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 16 publications
1
27
0
1
Order By: Relevance
“…10) and were distinctly decorated with cytokeratins (Figs. 8,9) in contrast to the atypical cells within the AFX, which were negative for cytokeratin but strongly positive for CD10 (Fig. 5).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…10) and were distinctly decorated with cytokeratins (Figs. 8,9) in contrast to the atypical cells within the AFX, which were negative for cytokeratin but strongly positive for CD10 (Fig. 5).…”
Section: Discussionmentioning
confidence: 96%
“…Similarly, tumors reported in the past as AFX appearing in non-sun-exposed skin of young individuals probably represent examples of atypical fibrous histiocytoma. 8 Immunocytochemical markers can help exclude these entities before the diagnosis of AFX is established. 9 The nonspecific lysosome marker CD68 has been shown to be variably positive in mononuclear (histiocyte-like and xanthomatous cells) and multinucleated cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kaddu et al (2) reported the presence of 1-15 pathologic mitoses per 10 high power field (HPF) (mean 3.4 per 10 HPF) (20/59 cases, 33.9%) and/ or geographic-like necrosis (7/59 cases, 11.9%) (2). Many reports have indicated positivity for factor Xllla (4-6), but negativity has also been reported in sotne cases (2,7,8). Garrido-Ruiz et al (6) and Wilk et al (8) reported that AFH was CD34-negative.…”
Section: Discussionmentioning
confidence: 98%
“…However, the tumoral Ki-67-positive proliferative cells lack Ki-M1p, a macrophagic marker, thus suggesting that macrophages are an accompanying background population. 7 The positivity of the cells of AFX to vimentin might suggest a mesenchymal origin. Accordingly, AFX has been shown to display myofibroblastic differentiation with the aid of electron microscopy.…”
Section: Introductionmentioning
confidence: 99%